2007
DOI: 10.1152/ajpcell.00567.2005
|View full text |Cite
|
Sign up to set email alerts
|

Apical electrolyte concentration modulates barrier function and tight junction protein localization in bovine mammary epithelium

Abstract: Quesnell RR, Erickson J, Schultz BD. Apical electrolyte concentration modulates barrier function and tight junction protein localization in bovine mammary epithelium. Am J Physiol Cell Physiol 292: C305-C318, 2007. First published August 2, 2006; doi:10.1152/ajpcell.00567.2005In vitro mammary epithelial cell models typically fail to form a consistently tight barrier that can effectively separate blood from milk. Our hypothesis was that mammary epithelial barrier function would be affected by changes in lumina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 45 publications
2
25
0
Order By: Relevance
“…Tight junction proteins, including zona occluden-1, occludin, and claudin-4, -8, and -12, have recently been described in bladder epithelial cells (1). Since in other epithelial cells claudins have been reported to be acutely physiologically regulated (3,4,34,46), it is possible that they, or other urothelial tight junction proteins might be regulated by hydration status. In this regard, prior studies have demonstrated dehydration-induced changes in renal collecting duct paracellular pathways resulting in higher permeability to water and nonelectrolytes (10) as well as altered rat renal papillary and renal pelvis epithelia (known to be similar in appearance and function to lower urinary tract epithelia) morphology in antidiuresis (5).…”
Section: Discussionmentioning
confidence: 99%
“…Tight junction proteins, including zona occluden-1, occludin, and claudin-4, -8, and -12, have recently been described in bladder epithelial cells (1). Since in other epithelial cells claudins have been reported to be acutely physiologically regulated (3,4,34,46), it is possible that they, or other urothelial tight junction proteins might be regulated by hydration status. In this regard, prior studies have demonstrated dehydration-induced changes in renal collecting duct paracellular pathways resulting in higher permeability to water and nonelectrolytes (10) as well as altered rat renal papillary and renal pelvis epithelia (known to be similar in appearance and function to lower urinary tract epithelia) morphology in antidiuresis (5).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies showed that TNF-α had no effect on the expression of the occludin protein (34)(35)(36), whereas others found that TNF-α or a mixture of cytokines (TNF-α, interferon-γ, interleukin-1β) reduced the amount and expression of occludin (30,37,38). In our study, TNF-α changed the expression of the special phosphorylated occludin protein in Caco-2 cells, supporting the conclusion that TNF-α can affect the expression of TJ proteins, disrupt the TJs and increase the permeability of the intestinal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…To date, investigations into fundamental aspects of mammary epithelial physiology have utilized mouse (5,6) and bovine (41) cell lines. Such studies have determined that fluid secretion across the apical membrane of murine mammary epithelial cells could be stimulated by inhibition of the epithelial Na ϩ channel or activation of the cystic fibrosis transmembrane conductance regulator Cl Ϫ channel (5) or Ca 2ϩ -dependent Cl Ϫ channels coupled to P2Y 2 purinoceptors (6).…”
mentioning
confidence: 99%
“…Such studies have determined that fluid secretion across the apical membrane of murine mammary epithelial cells could be stimulated by inhibition of the epithelial Na ϩ channel or activation of the cystic fibrosis transmembrane conductance regulator Cl Ϫ channel (5) or Ca 2ϩ -dependent Cl Ϫ channels coupled to P2Y 2 purinoceptors (6). More recently, the work of Quesnell et al (41) demonstrated that the electrolyte composition at the apical membrane of bovine mammary epithelial cells has profound effects on the distribution of the tight junction protein occludin. Thus these models demonstrate the complex and dynamic nature of transepithelial transport across the mammary epithelial barrier.…”
mentioning
confidence: 99%